Implementasi Manajemen Personil di Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan (PPPPTK) TK dan PBL - Neneng Komariah; Rohman Rohman; Hanafiah Hanafiah; Ida Tejawiani (IAIN Ternate, 2022)
Governance or personnel management is a part of management that deals with people. Personnel management is a field of scienc that studies how to provide a facility for development, work, and also a sense of work participation in an activity or activity. Employee competency development provides a very large advantage for a company because employees who have good competence according to needs will create work effectiveness and efficiency so that company/organization goals will be achieved as much as possible. However, some companies have not shown seriousness in carrying out personnel management properly so that the presence of employees seems to receive less serious attention. Whereas the employee element is the thing that determines the success of a company. For this reason, personal management needs to be managed as well as possible in a professional manner. Based on the above, it is very interesting to discuss how to manage personnel in a company/institution. This paper will discuss personnel management at the Center for the Development and Empowerment of Educators and Education Personnel (PPPPTK) for Kindergarten and Special Education (TK and PLB). With this paper, it is hoped that it will provide an overview of how to carry out personnel management so that it becomes a reference in managing the personnel of an institution